URGENSI ‘IDDAH BAGI SUAMI: DINAMIKA PERKEMBANGAN HUKUM: (Studi SE DIRJEN NO:P-005/DJ.III/HK.00.7/10/2021. Tentang Pernikahan dalam Masa Iddah Istri) - Mustakim, Ahmad; Fadhil Maarif (ADIDAS: Asosiasi Dosen Syari'ah STAI Darussalam Nganjuk, 2025)
This study responds to the discourse on the possibility of a waiting period (‘iddah) for men, positioning it as a reflection of ongoing legal development within Islamic law. Although not recognized in classical Islamic jurisprudence, this concept has gained attention following the issuance of Circular Letter No. P 005/DJ.III/Hk.00.7/10/2021 by the Directorate General of Islamic Community Guidance, which recommends a period of restraint for exhusbands before remarrying. While Islamic legal sources provide no textual or scholarly basis for a formal ‘iddah for men, the circular proposes a syibhul ‘iddah (quasi-‘iddah), grounded in the ethical rationale of preventing covert polygamy and protecting the sanctity of the former wife's waiting period. Legally, the circular serves only as a recommendation and carries no binding legal sanction. However, from the perspective of legal benefit (maslahah), it represents a progressive effort to adapt Islamic legal norms to contemporary social realities.Thus, syibhul ‘iddah may be viewed as part of modern Islamic legal discourse promoting justice and social welfare.